2020
DOI: 10.3390/ijerph17103613
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Effects of Honey and Its Constituent: An Evidence-Based Review of Laboratory Studies and Clinical Trials

Abstract: Cardiovascular disease is a major public health burden worldwide. Myocardial infarction is the most common form of cardiovascular disease resulting from low blood supply to the heart. It can lead to further complications such as cardiac arrhythmia, toxic metabolite accumulation, and permanently infarcted areas. Honey is one of the most prized medicinal remedies used since ancient times. There is evidence that indicates honey can function as a cardioprotective agent in cardiovascular diseases. The present revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Traditionally, honey was widely used for wound healing, as a food preservative, and against gastrointestinal illnesses [ 12 ]. According to recent literature, honey has revealed the presence of several beneficial effects for human health such as antibacterial [ 13 ], antioxidant, anti-inflammatory [ 14 ], and cardioprotective effects [ 15 ], with potentials as antiobesity [ 16 ] and neuroactivation associated with spatial memory [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, honey was widely used for wound healing, as a food preservative, and against gastrointestinal illnesses [ 12 ]. According to recent literature, honey has revealed the presence of several beneficial effects for human health such as antibacterial [ 13 ], antioxidant, anti-inflammatory [ 14 ], and cardioprotective effects [ 15 ], with potentials as antiobesity [ 16 ] and neuroactivation associated with spatial memory [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research has revealed that honey has a protective effect for the cardiovascular system by preventing the oxidative stress process of blood vessels, improving the plasma lipid constituents and attenuating elevation of heart function marker [209][210][211].…”
Section: Other Honeys Properties Valuable For Apitherapymentioning
confidence: 99%
“…Cardiovascular Diseases (CVDs) are the main cause of morbidity and mortality, accounting for 31% of all global deaths. Lipid abnormalities are the most important contributors to CVDs that include increased concentrations of Total Cholesterol (TC), Low Density Lipoprotein Cholesterol (LDL-C), and Triglycerides (TG) as well as decreased concentrations of High Density Lipoprotein Cholesterol (HDL-C) and its combinations (1) . Diet modification remains the main strategy for CVD management and lipid profile control.…”
Section: Introductionmentioning
confidence: 99%
“…CVD are the main cause of morbidity and mortality, accounting for 31 % of all global deaths. Lipid abnormalities are the most important contributors to CVD that include increased concentrations of total cholesterol (TC), LDL-cholesterol and TAG as well as decreased concentrations of HDL-cholesterol and its combinations (1) .…”
mentioning
confidence: 99%